Injection drug use infective endocarditis: clinical features and therapeutic challanges. (14th October 2021) - Scheggi, V; Ceschia, N; Vanni, F; Merilli, I; Sottili, E; Alterini, B; Marchionni, N; Stefano, P L
Abstract: Introduction: Injection drug use (IDU) is a known risk factor for infective endocarditis (IE) and is associated with frequent recurrences, but its prognostic impact is still debated. Moreover, the potential futility of surgery in this population is an unsolved matter. Purpose: We aimed to determine the clinical characteristics, the therapeutic strategy, and the prognostic impact of injection drug use IE (IDUIE). Method: We retrospectively included in the analysis 454 consecutive episodes of definite active IE admitted in a single surgical centre from January 2012 to December 2020; 14 out of them where a subsequent infective episode of the same patient. Results: IDUIE cases were 63 (13.8%), without significant proportional differences over time. IDUIE patients were significantly younger (43.95±10.12 vs 67.84±13.33, p 0.00) and presented fewer comorbidities (p<0.001). They were admitted with a first episode of IE only in 60.3% of cases vs 92.8% of non-IDU (p<0.001). Embolism was present at admission in a higher percentage (60.3 vs 38.4%, p<0.001). IDUIE was more frequently associated with spondylodiscitis (15.9 vs 7.4%, p=0.026). The infection was less frequently left-sided than in non-IDU patients (57.1 vs 97.2%, p<0.001) and was more often polimicrobic (12.7 vs 4.9%, p=0.015). Most patients were positive for Staphylococcus aureus (54.0 vs 12.8%, p<0.001), while Streptococci were significantly less frequent in patients with IDUIE (11 vs 25%, p=0.015). The proportion of patients undergoing surgery was similar among the two groups (85.5 vs 78.8%, NS). IDUIE patients treated medically for absence of surgical indication had a better survival than patients undergoing surgery for complicated IE (p<0.001). IDUIE was associated with a higher proportion of relapse during follow-up (28.3 vs 3.3%, p<0.001). It was not associated with higher mortality (Figure 1) but was an independent predictor of mortality in multivariable analysis including age (HR per unit 1.048, 95% CI 1.038–1.063, p=0.00) and drug abuse (HR 3.2, 95% CI 1.8–5.6, p=0.00; Figure 2). Among IDUIE patients, we did not find predictors of futility of surgery, not even multiple relapses. Conclusions: IDUIE represents a considerable proportion of overall cases of IE, mainly affecting young people. Staphylococcus aureus is the most common microbiologic agent. IDUIE is not associated with higher mortality but drug abuse is an independent predictor of mortality. Considering that patient with uncomplicated IE treated medically have a better prognosis, we should reserve surgery to patients with a strict indication for it. On the other hand, since there are no predictors of futility of surgery, all patients with a complicated IE should undergo surgery without delay. The main determinant of prognosis in these patients is not IE but drug abuse itself. For this reason, increased focus on addiction treatment following hospital discharge is mandatory to improve long term prognosis. Funding Acknowledgement: Type of funding sources: None.